Antibacterial activity and probiotic characterization of autochthonous Paenibacillus polymyxa isolated from Anabas testudineus (Bloch, 1792). (December 2017) - Midhun, Sebastian J.; Neethu, Sahadevan; Vysakh, A.; Arun, Damodaran; Radhakrishnan, E.K.; Jyothis, Mathew
Abstract: Microbial fish pathogens are prevalent in aquaculture. Control of bacterial fish pathogens is important and bio control of pathogenic bacteria is a novel field of study. The aim of this study was to evaluate the antagonistic activity of bacteria isolated from Anabas testudineus against potent fish pathogens. The cellular components/preparations and filtered cell free culture supernatants were effective against six fish pathogens. Altogether 110 strains were isolated from fish proximal and distal intestine, out of which 10 strains were selected through well diffusion method. From them a strain HGA4C having prominent antimicrobial activity was selected as candidate probiotic strain. The whole-cell product, heat-killed whole-cell product and the filtered broth were exhibited bactericidal activity against the tested pathogens. Among them cell free culture supernatant showed maximum inhibition. In addition, isolated candidate probiotic bacterium was capable of producing extracellular enzymes important for the digestion of food ingredients and was effectively grown in fish mucus obtained from Oreochromis niloticus. The strain tolerated gradient of bile juice secreted by the host and effectively produced biofilm. Analysis of 16S rDNA sequence revealed that isolated strain HGA4C was Paenibacillus polymyxa (MF457398.1). Furthermore intraperitoneal injection of the bacterium did not induce any pathological anomalies or mortalities in Oreochromis niloticus and disclosed the safety of this bacterium as a candidate probiotic in aquaculture. Highlights: Antagonistic activity of cellular components/preparations of HGA4C (MF457398.1) against fish pathogens and production of extra cellular enzymes by the bacterium were studied. The isolated bacterium was capable of growing in fish mucus and was tolerated bile juice. The bacterium produced biofilm on glass slide and biofilm production was compared with Aeromonas hydrophila . Intraperitoneal injection of the bacterium did not induce any pathological signs, symptoms or mortalities in Oreochromis niloticus . By BLAST and phylogenetic analysis strain HGA4C was identified as Paenibacillus polymyxa .